Modelling and simulation of spine layout design for flexible manufacturing system in digital factory platform / Phoon Sin Ye - Phoon , Sin Ye (2018)
This research presents the integration of information technology and digital three-dimensional (3D) modelling and simulation technology to build a digital factory in a virtual environment. Within the digital factory platform, a robotic work-cell and multi-stations flexible manufacturing system were developed to serve as an alternative decision-making tool in solving manufacturing system problems intuitively. The general framework for digital factory platform development was designed by utilizing various software such as 3D modelling, computer graphic programming, virtual reality (VR) and programming language. In the first phase of this study, a virtual robotic work-cell is built as a test model to determine the degree of interaction between the user and the digital factory, the capability of work-cell simulation, and the data collection from the digital factory platform to aid in decision-making. The digital platform enables intuitive interaction between the user and the virtual robotic work-cell while being capable of data collection. Through multiple simulation scenario of various process sequence of the same manufacturing part, simulation result shows that the difference in travel distance of part is up to 441.96% for different process sequence. In the second phase, a virtual loop layout model is developed and validated with a difference of 1.0% to 1.2% comparing to numerical results from literature study. A case study of allocation of shortcut conveyor in various positions within the developed virtual loop layout is then conducted to investigate the capability of digital factory platform to solve plant layout design problem. The digital factory platform simulated the impact of shortcut conveyor allocation in different position, and the results show that proper design of layout successfully reduced the loop congestion by 33.33% and total part travel distance by 10.64%. The developed digital factory platform in a virtual environment shows its capability to model and simulate manufacturing activities in 3D and to control and receive manufacturing data intuitively. The platform also acts as a scenario-based decision-making tool for optimizing process sequences and layout design.